Validity of Women's Clothing Patterns Learning Video With Cad Pattern Making - Reni Fitria; Rizkayeni Marta; Puji Hujria Suci; Ernawati Ernawati (JURNAL PENDIDIKAN DAN KELUARGA, 2022)
This research discusses the Validity of Women's Clothing Pattern Making Videos in the Fashion Pattern Construction Course. Online lectures require a media that can present and demonstrate the stages of making the basic pattern of women's clothing digitally so that students can observe the lecture material and can rewind if they don't understand without having to be disturbed by the signal/out of the internet data packets. This study uses the R&D (Research & Development) method with a 4D (four-D) model. The research stages consist of defining, designing, develop and disseminating. The production process of Women's Fashion Pattern Making Videos was designed with the CAD Pattern Making application and recorded with the Bandicam application. The results of the research are in the form of valid learning videos so that they can be used in the process of lecturing on Fashion Pattern Construction at IKK FPP UNP.